Response, resistance, deconstruction : reading and writing in/of three novels by John Updike - Keskinen, Mikko (1998)
The study explores the ways in which prose fiction can be seen to respond to or read itself, how writing allegedly explicates or reflects itself, and how resistance is realized both in reading and writing. These factors are investigated in John Updike's novels Rabbit Redux (1971), A Month of Sundays (1975), and The Coup (1978). The study is informed by narratology, reader-response, feminist and gender criticism, theories of self-reflexivity and resisting reading, and deconstruction. The communication between the narrator and narratee agents is conceived in terms of reading operations, especially commentary. The function of the interpreting character is thematized as that of the interpretant, the agent dramatizing and anticipating the actual reception of the work in which s/he appears. The prefiguration of interpretation is also analyzed with the help of such concepts as allegory of interpetation and transference. A deconstructive "methodology" is tentatively sketched on the basis of deconstructive critics' and theorists' readings. Features of selfreflexivity and metafictionality are presented and problematized with the help of narratology and deconstruction. Various instances of resistance, ranging from the ideological to the textual, are introduced and criticized. The term "resisting narratee" is tentatively introduced to account for both ideological criticism and narratology. To prepare the way from theory to application, such key presuppositions of narratology as communication, voice, and the narratee's gender and "race" are reread from the viewpoints of resistance and deconstruction. The commentary in the three Updike novels is classified on a functional and enunciative basis. The novels' narrators are definitely biased in relation to the narratees, which makes it possible to construct resisting narratees reading against the narrators' intentions and preferences. Each novel features allegories of interpretation (disputes between characters in Rabbit Redux and The Coup; sermons in A Month of Sundays), dramatizing and anticipating actual reception. The novels include moments of self-reflection of various kinds. The opposition between speech and writing is found and deconstructed in the novels. Each novel also has other oppositions (e.g. life/writing, act/ experience) which their logical articulation undermines. The portrait of Updike's fiction sketched in the study differs considerably from the generally established, mainstream readings of his work. Updike appears to be closer to American postmodemists than is usually acknowledged.